Methodology of Organizing Educational Lessons Based on Modern Approaches (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article discusses the need to organize education classes based on modern approaches, the principles of creating an educational ecosystem based on values for primary school students based on education classes, axiological approaches